Using a Critical Incident Scenario With Virtual Humans to Assess Educational Needs of Nurses in a Postanesthesia Care Unit. Issue 3 (July 2015) - White, Casey; Chuah, Joon; Robb, Andrew; Lok, Benjamin; Lampotang, Samsun; Lizdas, David; Martindale, James; Pi, Guillermo; Wendling, Adam
<x xml:space="preserve">Abstract</x> Introduction During critical incidents, teamwork failures can compromise patient safety. This study provides evidence that virtual humans can be used in simulated critical incidents to assess the learning needs of health professionals, and provide important information that can inform the development of continuing education programs in patient safety. We explored the effectiveness of information transfer during a devolving medical situation between postanesthesia care unit (PACU) nurses and a virtual attending physician. Methods We designed a three‐stage scenario: tutorial, patient transfer, and critical incident. We developed 2 checklists to assess information transfer: Critical Patient Information and Interprofessional Communication Skills. All participants were videotaped; 2 raters reviewed all videos and assessed performance using the checklists. Results Participants (n = 43) who completed all 3 stages scored 62.3% correct on critical patient information transfer and 61.6% correct on interprofessional communication skills. Almost 87% missed a fatal drug error. The checklists measured each item on a 1/0 (done/not) calculation. Additionally, no relationship was found between years of nursing experience and performance on either checklist. Discussion The PACU nurses in this study did not consistently share critical information with an attending (virtual) physician during a critical incident, and most missed a fatal dosage error. These findings strongly suggest a crucial need for additional structured team training among practicing health care teams, and they demonstrate the utility of using virtual humans to simulate team members.